The current status of Korean native pig production - Lee, Esther; Jang, Jae-Cheol; OH, Sang-Hyon (Journal of animal science and technology, 2023)
Korean native pigs (KNPs) have been one of the traditional livestock primarily raised in rural areas of Korea for centuries. KNPs have adapted to the climate and geography of the Korean Peninsula for a long time, exhibiting excellent adaptability even in challenging environments. For these reasons, the preservation and purification of KNPs are crucial in securing unique genetic resources. Therefore, this review covers the characteristics, production status, commercial value and potential breeding directions of KNPs. Unfortunately, there is still a long way to go for the improvement of KNPs. It is crucial to acknowledge the current challenges, identify the issues, and dedicate efforts to the breed's improvement. Each section of this comprehensive review will play an important role in integrating related research and data into the overall findings. In-depth discussions on the genetic diversity, productivity, genetic conservation, ecological roles, and sustainability of KNPs will be crucial components in the future of KNP business.